Surgical and radiological outcomes after posterior vertebral column resection according to the surgeon's experience. Issue 34 (August 2018) - Lee, Byoung Hun; Hyun, Seung-Jae; Han, Sanghyun; Kim, Ki-Jeong; Jahng, Tae-Ahn; Kim, Yongjung J.; Kim, Hyun-Jib
Abstract : Abstract: The purpose of this study was to estimate and analyze the radiological, surgical, and clinical results of posterior vertebral column resection (PVCR) according to the surgeon's experience. Although PVCR has been recognized as the most powerful surgical technique to correct severe spinal deformity, PVCR is a technically demanding procedure with a high complication rate. A retrospective review of the chart and radiographic data of 34 consecutive patients who received PVCR was carried out. According to the time period, the former and latter 17 patients were divided into group 1 and group 2, respectively. Patients' demographics, surgical, radiological/clinical outcomes, and complications were compared between the groups. The demographic data of the patients had no significant difference between the groups. The surgical time (492.5 ± 164.8 vs 350.5 ± 133.9 minutes, P  = .010), estimated blood loss (1294.1 ± 711.9 vs 974.1 ± 905.9 mL, P  = .045), and length of hospital stay (22.8 ± 12.9 vs 13.4 ± 3.9 days, P  = .017) were significantly reduced in group 2. The correction of the PVCR site (40.5° ± 13.3° vs 41.2° ± 23.7°, P  = .909), sagittal vertical axis (SVA, 81.9 ± 7.2 mm vs 77.9 ± 102.0 mm, P  = .904) were not different between the groups. The total number of complications (22 vs 10, P  = .031) and patients having complications (13 vs 7, P  = .039) were lower in group 2. Additional surgery was significantly lower in group 2 (13 vs 3, P  = .007). The clinical outcomes by revised Scoliosis Research Society-22 (SRS-22r) questionnaire were not different between the groups. Our series revealed that the complications after PVCR may reduce from 17 cases and surgical outcomes might be stabilized by 29 cases.